The Influence Of Service Quality And Religiosity On Customer Loyalty At Bank Syariah Indonesia - Ahmad Rafif Hubeis; Novita Ikasari (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of Service Quality and Religiosity on Customer Loyalty among customers of Bank Syariah Indonesia. The study employs a quantitative approach using an explanatory research method. The purposive sampling technique amounted to a total of 413 respondents who are Bank Syariah Indonesia’s customers. Data were collected through questionnaires using a five-point Likert scale. Data analysis was conducted using SPSS 27 to test three working hypothesis. The results showed that Service Quality and Religiosity have a positive and significant effect on Customer Loyalty when tested individualy. Consistently, the same result obtained when both independent variable were tested simultaneously. Service Quality and Religiosity significantly influenced Customer Loyalty. The findings indicate that customer loyalty of Bank Syariah Indonesia is influenced not only by service provision, but also by consumers’ perceived Islamic value. This is marked by the superior statistic result of religiosity toward customer loyalty when compared to that of service quality. Therefore, Bank Syariah Indonesia should strategize their marketing program to assimilate values and service quality, as well as design an effective communication strategy to increase customer retention.Keywords: Service Quality, Religiosity, Customer Loyalty, Islamic Banking, Bank Syariah Indonesia.